Factors associated with mortality in critically ill patients with COVID-19 - Rafaela dos Santos Charão de Almeida; André Klafke; Andresa Fontoura Garbini; Daniela dos Reis Carazai; Fernanda Costa dos Santos; Raquel Lutkmeier; Veridiana Baldon (Universidade de Santa Cruz do Sul, 2023)
Background and objectives: COVID-19 is a life-threatening disease. Recognizing the main characteristics of the disease and its main complications will help future interventions, care, and management of health services since territorial and population diversities directly influence health outcomes. Our main objective is to describe the clinical characteristics, outcomes, and factors associated with mortality of patients with COVID-19 admitted to the intensive care unit of a public and tertiary hospital. Methods: Cohort study, conducted from March 1 to September 30, 2020. Poisson regression was performed to investigate the variables of hospital treatment as potential risk factors for in-hospital mortality. Results: Of the 283 eligible patients in this study, the hospital mortality rate was of 41.7% (n=118). The most common outcomes were acute respiratory distress syndrome, nosocomial infection, and septic shock. Factors independently associated with increased risk of death were age greater than 51 years old (RR=1.7, 95%CI=1.0-2.8), especially over 70 years old (RR=2.9, 95%CI=1.7-2.8), current smoker (RR=1.8, 95%CI=1.1-2.9), requiring the use of inotrope (RR=1.4, 95%CI=1.0-2.0), and presenting potassium greater than 5.0 mEq/l on admission (RR=1.3, 95%CI=1.0-1.7).